Pengaruh Earning Per Share, Return On Asset dan Arus Kas terhadap Harga Saham pada Perusahaan yang terdaftar di Jakarta Islamic Index (JII) Periode 2013-2022 - Ardini, Luky; Amri, Andi (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
This study aims to examine the effect of Earning per Share, Return on Asset and Cash Flow on Stock Prices. The sample used in this study were companies listed on the Jakarta Islamic Index in the period 2013-2022. Testing used quantitative methods with a causality approach and purposive sampling technique, so that 7 companies were obtained and the number of samples obtained was 70 research samples. The data analysis method used is multiple linear regression analysis. The results of the test in this study found that Earning per Share has a positive effect on Stock Price, Return on Asset has a positive effect on Stock Price and Cash Flow has a negative effect on Stock Price.